O rozwoju szkolnych instytucji polonistycznych w dwudziestoleciu międzywojennym = On the development of Polish language school institutions at the twenty years interwar period - Cyniak, Eugeniusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the development of the most important Polish Scholar Institutions serving for the Polish School at the twenty years interwar period. The subject of the description became the activity of the ministerial and curator Institutions, of the didacticians of Polish Language, of Central Didactic Laboratories, of Polish Scholar courses, methodical Centres, periodical "Polonista", Polish Scholar Clubs and Associations, including with the Polish Scholars Company of the Polish Republic.
Keywords: szkolnictwo polskie - 1918-1939